Inside Cover Picture: Iron–Nitrogen Coordination in Modified Graphene Catalyzes a Four‐Electron‐Transfer Oxygen Reduction Reaction (ChemElectroChem 5/2014). Issue 5 (29th April 2014) - Kamiya, Kazuhide; Koshikawa, Hiroyuki; Kiuchi, Hisao; Harada, Yoshihisa; Oshima, Masaharu; Hashimoto, Kazuhito; Nakanishi, Shuji
<x xml:space="preserve">Abstract</x> The inside cover picture shows the high density of Fe/N structures that can be introduced into graphene sheets by very short‐duration heat treatment (<1 min). The resulting Fe/N‐modified graphene shows the high number of electrons transferred in the oxygen reduction reaction; see the Full Paper by K. Hashimoto, S. Nakanishi et al. on page 877 (DOI: 10.1002/celc.201300181).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>